The Integrity of the Body of Christ : Boundary Keeping as Shared Responsibility. - Mahlberg, Arden (Wipf and Stock Publishers, 2016)
For religious communities to have integrity and credibility they must flourish as places of love and respect. Every aspect of church life is defined and protected by essential boundaries: boundaries around space, time, thought, speech, will, emotion, and behavior--both for clergy and church members. Lack of awareness and attention to boundary keeping diminishes the integrity of the church and harms its mission, whereas insight and vigilance about best practices lend freedom and energy to the calling of the church to care for others and to reach out to the world. In a flourishing Christian comm.